Study on Noise and Its Removal Techniques - Pious, Mary Sruthy; Azath, M (International Journal of Computer Sciences and Engineering, 2015)
Removal of noise is an essential and challengeable operation in image processing. Before performing any process in the image, it must be first restored. Images may be corrupted by noise during image acquisition and transmission. Nature of the noise removal depends upon the type of the noise corrupting the image. In an image there will be different type of noises like impulse noise, adaptive white Gaussian noise, short noise, quantization noise, film grain, these one or more are coupled together to form a mixed noise. To remove this type of noise there is a novel method comprises two stages: the first stage is to detect the noise in the image. In this stage, based on the intensity, the pixels are roughly divided into “noise-free pixel” and “noisy pixel”. Then, in the second stage it is to eliminate the noise from the image. In this, only the “noise-pixels” are processed. The “noise free pixels” are copied directly to the output image. The survey aims to study the different types of noises and noise removal techniques of an image.